2017
DOI: 10.1097/md.0000000000007513
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of assays for circulating tumor cells in hepatocellular carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
1
28
0
3
Order By: Relevance
“…Detection of CTCs is associated with poor overall survival and relapse-free survival [91] . In addition to that, CTCs positivity is significantly correlated with serum AFP level, vascular invasion and TNM stage which can reflect the histopathological status of HCC [92] . According to a recent meta-analysis of more than 20 studies, the CTC is not used as a sole indicator for diagnosis instead associated with poor clinical and pathological features [92] .…”
Section: Ctcsmentioning
confidence: 90%
“…Detection of CTCs is associated with poor overall survival and relapse-free survival [91] . In addition to that, CTCs positivity is significantly correlated with serum AFP level, vascular invasion and TNM stage which can reflect the histopathological status of HCC [92] . According to a recent meta-analysis of more than 20 studies, the CTC is not used as a sole indicator for diagnosis instead associated with poor clinical and pathological features [92] .…”
Section: Ctcsmentioning
confidence: 90%
“…Given the highly vascularized liver environment, the use of CTCs as biomarkers for HCC has been under scrutiny. For instance, two different meta-analyses have shown that CTCs associate with a poor prognosis and poor clinicopathologic parameters in HCC [58,59]. Epithelial-mesenchymal-mixed CTCs seem to play an important role in epithelial-mesenchymal transition in HCC, mixed CTCs appearing to play a vital factor for intrahepatic metastasis, and mesenchymal CTCs having the potential to predict extrahepatic metastasis [60].…”
Section: Circulating Tumor Cells and Extracellular Vesiclesmentioning
confidence: 99%
“…A correlation exists between the postoperative early recurrence of HCC and mesenchymal CTCs [32,33]. An elevated number of CTCs is associated with unfavorable clinicopathologic characteristics responsible for poor prognosis in patients with HCC [34]. An increase in the number of postoperative CTCs when compared to the number of preoperative CTCs is associated with lower survival and higher recurrence among patients with low AFP levels and cirrhosis [35].…”
Section: Discussionmentioning
confidence: 99%